Monetary Policy, Product Market Competition and Growth. (16th May 2019) - Aghion, Philippe; Farhi, Emmanuel; Kharroubi, Enisse
Abstract : In this paper we argue that monetary easing fosters growth more in more credit‐constrained environments, and the more so the higher the degree of product market competition. Indeed, when competition is low, large rents allow firms to stay on the market and reinvest optimally, no matter how funding conditions change with aggregate conditions. To test this prediction, we use industry‐level and firm‐level data from the euro area to look at the effects on sectoral growth and firm‐level growth of the unexpected drop in long‐term government bond yields following the announcement of the Outright Monetary Transactions programme (OMT) by the European Central Bank. We find that the monetary policy easing induced by OMT contributed to raising sectoral (firm‐level) growth more in more highly leveraged sectors (firms), and the more so the higher the degree of product market competition in the country (sector).